2007
DOI: 10.1111/j.1945-5100.2007.tb00548.x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of oceanic impact‐induced large water waves—Re‐evaluation of the tsunami hazard

Abstract: available online at http://meteoritics.org Characteristics of oceanic impact-induced large water waves-Re-evaluation of the tsunami hazard Abstract-The potential hazard of a meteorite impact in the ocean is controversial with respect to the destructive power of generated large ocean waves (tsunamis). We used numerical modeling of hypervelocity impact to investigate the generation mechanism and the characteristics of the resulting waves up to a distance of 100-150 projectile radii. The wave signal is primarily … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 38 publications
(64 reference statements)
0
46
0
Order By: Relevance
“…6d) followed by a final stage of "oscillating resurge." At craters with target water depths greatly exceeding the height of the rim of the crater forming in the seabed, this anti-resurge may cause an outwards propagating tsunami-wave (Wünnemann et al 2007). Here we deal with the resurge deposits within and in direct proximity of the crater in the seabed, and not with distal tsunami deposits.…”
Section: Resurge Deposits-definition and General Descriptionmentioning
confidence: 99%
“…6d) followed by a final stage of "oscillating resurge." At craters with target water depths greatly exceeding the height of the rim of the crater forming in the seabed, this anti-resurge may cause an outwards propagating tsunami-wave (Wünnemann et al 2007). Here we deal with the resurge deposits within and in direct proximity of the crater in the seabed, and not with distal tsunami deposits.…”
Section: Resurge Deposits-definition and General Descriptionmentioning
confidence: 99%
“…[12] iSALE is validated against experimental studies of hypervelocity impacts and other hydrocodes [Pierazzo et al, 2008] and used successfully in modeling of meteorite impact wave generation studies [Weiss et al, 2006;Wünnemann et al, 2007].…”
Section: Hydrocode Modelingmentioning
confidence: 99%
“…Wünnemann et al (2007) showed that, in oceanic impacts, rim waves are the predominant waves in shallow-water impacts but decay rapidly in deep-ocean impacts. Collapse waves, on the other hand, are not a factor in shallow-water impacts, where the crater rim tends to stop water from flowing back into the crater and be affected by crater collapse, but they become the dominant waves in deepocean impacts.…”
Section: Tsunamimentioning
confidence: 99%
“…The presence of sub-micrometre dust at the top of the atmosphere may reflect downward some of the IR radiated upward (Goldin and Melosh, 2009), and increase ground radiation. On the other hand, numerical simulations by Artemieva and Morgan (2009) indicate that a significant fraction of the K-Pg critical parameter is d/H, the ratio of impactor diameter d and ocean depth H. Wünnemann et al (2007) found that the smaller the d/H is the more rapidly the wave amplitude is attenuated with distance. For d/H < 0.4, rim waves are quickly dissipated and the main impact-generated wave is a collapse wave.…”
Section: Distal Ejecta and Thermal Effectsmentioning
confidence: 99%
See 1 more Smart Citation